The Detection of Pb2+ Using Glutathione Capped Mn Doped ZnS QDs - Bian, Wei; Zhang, Hao; Wang, Fang; Ma, Jing; Wei, Yanli; Shuang, Shaomin; Cai, Zongwei (Current Analytical Chemistry, 2015)
L-glutathione decorated Mn doped ZnS QDs (GSH-Mn: ZnS QDs) were synthesized in aqueous solution. The characterization of as-prepared QDs was carried out through fluorescence, ultraviolet-visible absorption (UV-vis), TEM and Fourier transform infrared spectroscopy (FTIR). Pb2+ had obvious quenching effect on the fluorescence intensity of GSH-Mn: ZnS QDs. Under optimal factors, a nice linear relationship between the fluorescence response and the concentration of Pb2+ was established from 0.025µM to 15.5µM range with a correlation coefficient of 0.9981 and the detection limit is 0.018µ. This probe was triumphantly made use of the detecting of Pb2+ in tap and pond water. At the same time, it was preliminary inferred that the fluorescence quenching way of Pb2+ to QDs was dynamic quenching. The present study provides a simple, low-cost route toward production of GSH-Mn: ZnS QDs for chemo/bio sensing and other adhibition.
Keywords: fluorescence quenching